Global weak solutions for the two-dimensional magnetohydrodynamic equations with partial dissipation and diffusion. (October 2016) - Regmi, Dipendra
Abstract: In this paper, we consider the two-dimensional magnetohydrodynamic equations. We establish global weak solution for MHD equations with partial dissipation and vertical diffusion. We also obtain a regularity condition.